MODERN PRINCIPLES OF CHRONIC HEART FAILURE (Modern education and development, 2025)
The problem of chronic heart failure is currently becoming increasingly important not only for clinical medicine, but also for the entire healthcare system and society as a whole. An increase in life expectancy, improvement of medical care for patients suffering from various cardiovascular diseases (CVD), lead to an increase in the number of patients with chronic heart failure (CHF). Having achieved significant success in terms of combating acute cardiovascular diseases, improving treatment and preventive care for patients with CHF will bring the system of care for patients with CVD to a higher level. The main element of the new design is the creation of a specialized service to help patients with CHF. This review is devoted to the discussion of modern trends in heart valve replacement.